Biotransformation of brewer’s spent grain and application as a food ingredient in extruded breakfast cereals - Thorvaldsson, Mira (My University, 2020)
Brewers' spent grain (BSG) is a beer brewing by-product, that mainly consists of fibers (more than 50%) and proteins (up to 30%). BSG has, due to its content, a big potential to be used in the food industry but it is currently used as animal feed or discarded. To improve BSG's usability as a food ingredient bioprocessing with slime producing lactic acid bacteria has been used in this project. Incorporation of fermented BSG as a food ingredient in breakfast cereals has been performed with extrusion method. A process and recipe have been developed to produce breakfast cereal prototypes. Evaluations of the taste and texture of the breakfast cereal prototypes have been performed with texture measurements but mainly with consumer panels (focus groups). The final breakfast cereal prototypes produced for the last focus group were all with 30% fermented BSG. The BSG were from three different breweries, Dugges, Senson and Peroni, and the fermentation was performed with and without slime production by the lactic acid bacteria. The most preferred breakfast cereal prototype was with BSG from the brewery Dugges and fermented with slime producing lactic acid bacteria. The conclusion of this master thesis project was that it is possible to make breakfast cereal products with a content of 30% fermented BSG with extrusion method with a pleasant taste and texture.
Keywords: Brewers spent grains; Extrusion; Breakfast cereals; Fermentation; Lactic Acid Bacteria